The Penelopiad: (meta)re-visão crítica - Souza, Juliana Cristina Terra de (Universidade Federal de São Carlos, 2025)
This study aims to demonstrate how The Penelopiad (2006), written by Canadian author Margaret Atwood, can be understood as a critical meta-revision in which the novel simultaneously draws upon the classical tradition and feminist revisionist models while also questioning and transforming their paradigmatic elements. The analysis seeks to identify the conditions of possibility and the social significance of the new re-vision proposed by Atwood, exploring the political unconscious represented in the book – from the perspective of Fredric Jameson’s (1992) – in relation to the social condition of women in contemporary society. For this purpose, the research employs the concept of metacommentary (Jameson, 1992) as applied to interpretive codes related to texts engaged in critical revision of tradition, combined with an analysis of the horizons of interpretation and the strategies of containment present in the corpus, supported by Jameson’s theoretical and methodological framework.
The Penelopiad: critical (meta)re-vision
Keywords: Leitura política; Re-visão; The Penelopiad.; Political reading; Re-vision; The Penelopiad; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS; 4. Educação de Qualidade; 5. Igualdade de Gênero